Analisis Keamanan Data Pelanggan dalam Menghadapi Tantangan Penggunaan Marketplace - Dewantara, Rizki; Bintang, Rauhulloh Ayatulloh Khomeini Noor; Gatra, Rahmadhan (UIN Sunan Kalijaga Yogyakarta, 2024)
The advent of the digital economy makes commerce more accessible to everyone. Example: an online marketplace app that simplifies buying and selling. The marketplace app's useful features and ease of use attract many users. The marketplace app's functionality and convenience have been enhanced to meet consumer expectations and prioritize consumer data protection. This study investigates how customers protect their data when shopping online and utilizing marketplace apps. Environmental and social influences, personal data security facilities, the goal of utilizing the marketplace, and awareness of customer data security when using the marketplace application were asked of 70 random sample participants. The questionnaires had 16 Guttman scale questions. According to the report, 81.42% of customers trust the marketplace app to protect their data. Likewise, 88.57% of customers strongly believe that the marketplace application they use secures their personal information, indicating that this is related to their marketplace service needs.